2011
DOI: 10.1037/a0022845
|View full text |Cite
|
Sign up to set email alerts
|

Prospective memory in an air traffic control simulation: External aids that signal when to act.

Abstract: At work and in our personal life we often need to remember to perform intended actions at some point in the future, referred to as Prospective Memory. Individuals sometimes forget to perform intentions in safety-critical work contexts. Holding intentions can also interfere with ongoing tasks. We applied theories and methods from the experimental literature to test the effectiveness of external aids in reducing prospective memory error and costs to ongoing tasks in an air traffic control simulation. Participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
100
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 39 publications
(114 citation statements)
references
References 48 publications
14
100
0
Order By: Relevance
“…Strategic monitoring is typically only activated when the appropriate context to perform a prospective memory task is reached (cf. Loft, Smith, & Bhaskara, 2011;Marsh, Hicks, & Cook, 2006;Meier et al, 2006). In an activity-based task, no interruption of the ongoing task is necessary because the appropriate moment is by definition signaled by the end of an activity.…”
mentioning
confidence: 99%
“…Strategic monitoring is typically only activated when the appropriate context to perform a prospective memory task is reached (cf. Loft, Smith, & Bhaskara, 2011;Marsh, Hicks, & Cook, 2006;Meier et al, 2006). In an activity-based task, no interruption of the ongoing task is necessary because the appropriate moment is by definition signaled by the end of an activity.…”
mentioning
confidence: 99%
“…We use existing concepts in standard information-processing models to provide insight into why resource allocation is not fully adjusted in nonfocal compared to focal tasks. As discussed later, it is also important for practical purposes to understand the task demand factors that influence resource allocation and the subsequent probability of PM error (Kliegel, Jäger, & Phillips, 2008;Loft, Smith, & Bhaskara, 2011).…”
mentioning
confidence: 99%
“…Past studies have revealed that contextual cues in the environment often prompt retrieval of a future intention (Harris & Wilkins, 1982, Henry et al, 2012Kuhlmann & Rummel, 2014;Kvavilashvilli & Fisher, 2007), and the present research extended this finding with the observation that contextual cues can trigger retrieval of the future intention, thereby prompting participants to overtly monitor for prospective memory targets. Salient external cues have been shown to be helpful to adults (Guajardo & Best, 2000) in a variety of laboratory studies (Einstein & McDaniel, 1996;Kim & Mayhorn, 2008;Villa, 1998), including investigations of air traffic control (Loft et al, 2011). In particular, external aids were helpful when they appeared in the context of the prospective memory targets.…”
Section: Discussionmentioning
confidence: 99%
“…Both self-report and behavioral data suggest that environmental cues can serve as a reminder for a prospective memory intention (Harris & Wilkins, 1982;Henry, Rendell, Phillips, Dunlop, & Kliegel, 2012;Kvavilashvili & Fisher, 2007) and that environmental cues can be used to support prospective memory in laboratory simulated air traffic control scenarios (Loft, Smith, & Bhaskara, 2011). It remains unclear exactly how environmental cues interact with the cognitive mechanisms supporting prospective memory, although some research has suggested that people will adjust how they allocate attention to the prospective memory task if they are instructed about contextual cues that will accompany the prospective memory target (Kuhlmann & Rummel, 2014).…”
mentioning
confidence: 99%